Why Government Turns to AI – What Citizens Believe and How it Matters. Survey Evidence from Germany and the Netherlands - Pascal D. Koenig (The American Review of Public Administration, 2026)
What do citizens believe to be guiding motives behind the increasing adoption of artificial intelligence (AI) in government, and how are these beliefs related to AI acceptance? Drawing on moral judgment theory, the present article argues that the presumed intentions behind AI use matter for citizens’ evaluations of this use. It studies how citizens’ beliefs about public values motives are associated with AI acceptance across four types of AI use that involve different citizen-state relationships. The analysis uses survey data from 2072 respondents in Germany and the Netherlands and finds that that acceptance of AI use hinges on whether citizens believe that government AI adoption is guided by performance-related values – efficiency, effectiveness, productivity. Beliefs about procedure-related public values motives – impartiality, equal treatment, transparency – do not matter. The findings have implications for how to engender public support for government AI use and for understanding imbalances in public values driving AI adoption.